What do we actually know about the biomechanics of pregnancy and labour? A systematic scoping review - Anastasia Topalidou; Lauren Haworth; Raeesa Jassat; Morgan Hawcroft-Hurst (PLoS ONE, 2025)
Pregnancy and childbirth involve profound biomechanical transformations, adaptations, and functional demands on the maternal body. Although biomechanical complications have been identified as a major contributor to maternal morbidity and mortality, this remains one of the most under-researched areas in perinatal health. This systematic scoping review aimed to map and synthesise existing literature on the biomechanics of pregnancy and labour. Following Arksey and O’Malley’s framework and PRISMA-ScR guidance, comprehensive searches of MEDLINE, EMBASE, and MIDIRS were conducted up to May 2025. Eligible sources were peer-reviewed empirical studies assessing musculoskeletal, kinematic, kinetic, postural, or dynamic parameters in pregnant or labouring women. Titles, abstracts, and full texts were screened against predefined eligibility criteria. Data were charted using a structured extraction form and synthesised narratively across key biomechanical themes. Eighty-seven studies were included, all of which focused on pregnancy. No studies conducted during labour were identified. Most were observational with small sample sizes and limited diversity. Ethnicity was reported in only one study. Four key themes emerged: (1) Posture and spinal curvature, (2) Gait and locomotor analysis, (3) Functional tasks and interventions, and (4) Balance and stability. Findings showed high individual variability and no consistent biomechanical pattern across pregnancy. Real-world, neuromuscular, and labour-related biomechanics remain largely unexplored. This review underscores a critical gap in perinatal research: while biomechanical adaptations during pregnancy have been increasingly studied, labour remains entirely unexamined from a biomechanical perspective. Current evidence is fragmented, methodologically narrow, and lacks diversity, offering limited clinical relevance. We are effectively operating in a biomechanical vacuum, without empirical data to guide safer, more efficient, and personalised birth practices. Existing clinical approaches rely heavily on tradition, anecdotal experience, and untested theoretical assumptions. Addressing this evidence void, particularly in labour biomechanics and ethnic representation, is essential to improve perinatal outcomes and support equity in maternal care.